Multi-Locus Genome-Wide Association Studies to Characterize Fusarium Head Blight (FHB) Resistance in Hard Winter Wheat - Zhang, Jinfeng; Gill, Harsimardeep S.; Halder, Jyotirmoy; Brar, Navreet K.; Ali, Shaukat; Bernardo, Amy; Amand, Paul St.; Bai, Guihua; Turnipseed, Brent; Sehgal, Sunish K. (Frontiers in Plant Science, 2022)
Fusarium head blight (FHB), caused by the fungus Fusarium graminearum is an important disease of wheat that causes severe yield losses along with serious quality concerns. Incorporating the host resistance from either wild relatives, landraces, or exotic materials remain challenging and has shown limited success. Therefore, a better understanding of the genetic basis of native FHB resistance in hard winter wheat (HWW) and combining it with major quantitative traits loci (QTLs) can facilitate the development of FHB resistant cultivars. In this study, we evaluated a panel of 257 breeding lines from the South Dakota State University (SDSU) breeding program to uncover the genetic basis of native FHB resistance in the US hard winter wheat. We conducted a multi-locus genome-wide association study (ML-GWAS) with 9,321 high-quality single nucleotide polymorphisms (SNPs) covering all 21 wheat chromosomes. A total of six distinct MTAs were identified for the FHB disease index (DIS) on five different chromosomes including 2A, 2B, 3B, 4B, and 7A. Further, eight MTAs were identified for Fusarium damaged kernels (FDK) on six chromosomes 3B, 5A, 6B, 6D, 7A, and 7B. Out of the 14 significant MTAs, ten were found in previously reported regions for FHB resistance in different wheat classes and were validated in HWW while four MTAs represent likely novel loci for FHB resistance. The additive effect of favorable alleles of the identified MTAs was significant as the combination of these alleles resulted in lower mean DIS and FDK scores. Candidate gene analysis for two important MTAs identified several genes with putative proteins of interest and these genes need further investigation. The current study sheds light on the genetic basis of native FHB resistance in the US HWW germplasm and the resistant lines and MTAs identified in this study will be useful resources for FHB resistance breeding via marker-assisted selection.